Nutritional evaluation of wild plant Cissus rotundifolia - MOHAMED KORISH (Chiriotti Editori, 2016)
This study aimed to evaluate the nutritional and antinutritional components of Cissus rotundifolia leaves. They contain an appreciable amount of protein (12.5%db), fat (7.45% db), crude fiber (8.34 % db) and minerals (16.32%db). The protein fraction contains a relatively high level of essential amino acids, which accounted for 44.3% of the total amino acids. The fat contains a high concentration of unsaturated fatty acids that comprises 55.1% of total fatty acids. The mineral profile is composed of macro- and microelements. The antinutritional factors oxalate, phytate, tannins and cyanogenic glycosides are present at very low concentrations. Cissus rotundifolia leaves can be considered a potential source of nutritional components for healthy food purposes.